Relationship of Socio-Economic Characteristics with Level of Farmers’ Awareness about Climate Change Effect on Water Resources (Indian Journal of Extension Education, 2018)
The present study was conducted to know the relationship of socio-economic variables with the level of awareness of farmers. The study was conducted in three villages of Punjab with a sample of 120 famers which was drawn randomly from villages Talwandi Khurd, Sandhuan and Ran Singhwala. The results indicated that most of the respondents belonged to the middle age group (40.83%), matriculates (23.33%), had joint family (77.5%) and had family size of 2-6 members (68.33%). The data further showed that majority of the farmers had high level of awareness regarding effect of climate change on water resources (71.67%) and effect of heavy rainfall (57.5%). Results further revealed that awareness regarding reasons of climate change was associated with family size (268.0), farm area (563.72) and mass media exposure (201.62) at one percent level of significance. The study recommends that there is a need to create awareness among farmers and extension personnel should play important role in educating the farmers about climate change, mitigation and adaptation.